2020
DOI: 10.3390/ijms21041184
|View full text |Cite
|
Sign up to set email alerts
|

Beyond PSA: The Role of Prostate Health Index (phi)

Abstract: Background: Widespread use of prostate specific antigen (PSA) in screening procedures allowed early identification of an increasing number of prostate cancers (PCas), mainly including indolent cancer. Availability of different therapeutic strategies which have a very different impact on the patient's quality of life suggested a strong need for tools able to identify clinically significant cancer at diagnosis. Multi-parametric magnetic resonance showed very good performance in pre-biopsy diagnosis. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 67 publications
1
53
0
2
Order By: Relevance
“…Summarizing the available scientific data, it is concluded that phi and PHID could help to improve individual risk assessment for early particularly clinically significant PCa detection, to reduce unnecessary biopsies, either may help to select patients eligible for active surveillance and may play a role in treatment decision-making [32].…”
mentioning
confidence: 99%
“…Summarizing the available scientific data, it is concluded that phi and PHID could help to improve individual risk assessment for early particularly clinically significant PCa detection, to reduce unnecessary biopsies, either may help to select patients eligible for active surveillance and may play a role in treatment decision-making [32].…”
mentioning
confidence: 99%
“…Currently, FDA-approved assessments, including Progensa-PCA3 and prostate health index (PHI) tests, provide informative recommendations for repeated prostate biopsy among men with a previous negative biopsy [ 20 , 38 , 39 , 40 ]. The PHI test is also helpful in both reducing unnecessary initial biopsies in biopsy-naïve patients and predicting the pathological aggressiveness at radical prostatectomy [ 40 ]. Despite the above well-established instruments, we hope to identify additional biomarkers to improve the decision-making strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It is now recommended by clinical guidelines for patients with elevated tPSA, especially for patients with tPSA between 2.0 and 10.0 ng/ml (4)(5)(6)(7). Synthesizing several published results, using phi can reduce the number of unnecessary biopsies with good sensitivity and detect clinically significant PCa; thus, phi might play an important role reducing overdiagnosis and overtreatment in urologic practice (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The cost of phi testing varies among different countries and regions from $35 to $370 (United States dollars) (9)(10)(11)(12)(13)(14). Several cost-effectiveness analyses of phi have been performed in the United States, Europe, and Hong Kong, which are all based on the population-based screening models using a specific phi cutoff (11,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%